ACTR-07. LONG-TERM OUTCOMES FROM INTERGROUP NCCTG 86-72-51 (ALLIANCE): FINAL REPORT OF A PHASE III PROSPECTIVE RANDOMIZED TRIAL OF HIGH DOSE VERSUS LOW DOSE RADIATION IN ADULT SUPRATENTORIAL LOW-GRADE GLIOMA. (11th November 2019) - Breen, William; Keith Anderson, S; Carrero, Xiomara; Brown, Paul; Ballman, Karla; O'Neill, Brian; Curran, Walter; Abrams, Ross; Laack, Nadia; Levitt, Ralph; Galanis, Evanthia; Buckner, Jan; et al.
Abstract: PURPOSE: To provide a final update on oncologic and cognitive outcomes of high dose versus low dose radiation for low-grade glioma. METHODS: Between 1986 and 1994, 203 patients with supratentorial low grade glioma were randomized to 50.4 Gy in 28 fractions versus 64.8 Gy in 36 fractions after any degree of resection. Histologic subtype was oligodendroglioma (71%) or astrocytoma (29%). Primary outcome was overall survival (OS). Cognitive status was followed using Folstein Mini-Mental State Examination (MMSE). RESULTS: For the entire cohort of 203 patients, median OS was 8.4 years (95% CI: 7.2 – 10.8). Median progression-free survival (PFS) was 5.2 years (95% CI: 4.3 – 6.6). Median follow-up is 17.2 years for the 33 patients still alive. High-dose radiation did not improve OS (15-yr OS: 22.4% vs. 24.9%, log rank p=0.978) or PFS (15-yr PFS: 15.2% vs. 9.5%, p=0.7142). OS was significantly better for patients with pre-operative tumor diameter < 5 cm (15-yr OS: 39.4% vs. 15.2%, p< 0.001), baseline MMSE > 27 (15-yr OS: 27.3% vs. 9.8%, p=0.001), and for patients who underwent gross total resection (GTR) (15-yr OS: 39.3% GTR vs. 16.4% subtotal resection vs. 24.5% biopsy only, p=0.0119). PFS was improved for patients with oligodendroglioma versus astrocytoma (15-yr PFS: 13.8% vs. 8.6%, p=0.0221). PFS was also improved for patients with pre-operative tumor diameter < 5 cm, patients who had GTR, and patients with baseline MMSE > 27. For patients who had normal MMSE at baseline, at 7 years only 1 patient (5%) had a clinically significant decrease in MMSE from the previous time point, with the remainder (95%) stable. None had decrease in MMSE at 10, 12, or 15 years. CONCLUSIONS: Long-term follow-up indicates no benefit to high-dose over low-dose radiation for low-grade gliomas. Minimal late decline in cognitive function after radiation was seen by MMSE. SUPPORT: U10CA180821, U10CA180882. https://acknowledgments.alliancefound.org